2014
DOI: 10.14366/usg.14017
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast-enhanced endoscopic ultrasonography: advance and current status

Abstract: Endoscopic ultrasonography (EUS) technology has undergone a great deal of progress along with the color and power Doppler imaging, three-dimensional imaging, electronic scanning, tissue harmonic imaging, and elastography, and one of the most important developments is the ability to acquire contrast-enhanced images. The blood flow in small vessels and the parenchymal microvasculature of the target lesion can be observed non-invasively by contrast-enhanced EUS (CE-EUS). Through a hemodynamic analysis, CE-EUS per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In conclusion, CFD estimations of the velocity field and flow reduction in aneurysms treated with a flow-diverting stent were verified by Doppler ultrasonography measurements in patientspecific phantom models, using proper ranges of hemodynamic parameters such as density and viscosity [ 16 , 30 ]. This combination of CFD and ultrasonography may constitute a feasible and reliable technique for predicting flow diversion in intracranial aneurysms after flow-diverter treatment, proving again that ultrasonography is a valuable technique in the cardiovascular system as well as the gastrointestinal setting [ 32 ]. In order to establish correlations with clinical outcomes, further studies are required to identify the precise modifications in the flow and the hemodynamics after a flowdiverter stent graft or PED is deployed.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, CFD estimations of the velocity field and flow reduction in aneurysms treated with a flow-diverting stent were verified by Doppler ultrasonography measurements in patientspecific phantom models, using proper ranges of hemodynamic parameters such as density and viscosity [ 16 , 30 ]. This combination of CFD and ultrasonography may constitute a feasible and reliable technique for predicting flow diversion in intracranial aneurysms after flow-diverter treatment, proving again that ultrasonography is a valuable technique in the cardiovascular system as well as the gastrointestinal setting [ 32 ]. In order to establish correlations with clinical outcomes, further studies are required to identify the precise modifications in the flow and the hemodynamics after a flowdiverter stent graft or PED is deployed.…”
Section: Discussionmentioning
confidence: 99%
“…There are several commercially available UCAs approved by the food and drug administration (FDA) for clinical use in the US, for example Definity, Sonovue, Lumason, and Imagent. These UCAs are prepared through simple hand agitation or mechanical vibration within 60 s. Secondly, a UCA organized by protein or polymers that features a rigid and stable shell structure has a greatly enhanced circulation time and applicability . The FDA‐approved proteinaceous UCAs, Albunex and Optison, have been reported to be successfully prepared by using an ultrasonic synthesis process for contrast echocardiography.…”
Section: Functions and Research On Ultrasound Contrast Agents (Ucas)mentioning
confidence: 99%
“…These UCAs are prepared through simple hand agitation or mechanical vibration within 60 s. Secondly, a UCA organized by protein or polymers that features a rigid and stable shell structure has a greatly enhanced circulation time and applicability. [20] The FDA-approved proteinaceous UCAs, Albunex and Optison, have been reported to be successfully prepared by using an ultrasonic synthesis process for contrast echocardiography. Specifically, under certain sonication conditions (20 kHz and 80 W at 20 °C or 50 °C), after inducing superoxide radicals (O 2 − ), proteins such as albumin and hemoglobin can be crosslinked between their thiol groups and cysteine residues by the formation of disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The blood flow in small vessels and the parenchymal microvasculature of the target lesion can be observed non-invasively by contrast-enhanced EUS (CE-EUS). Through a hemodynamic analysis, CE-EUS permits the diagnosis of various gastrointestinal diseases and differential diagnoses between benign and malignant tumours [18]. It was shown that in mediastinal LNs CE-EUS can detect a filling defect, which is a typical sign of malignant lymphadenopathy, with a sensitivity of 100% and a specificity of 84% [19].…”
Section: Tissue Harmonic Echo (The) and Contrast-enhancement In Ebusmentioning
confidence: 99%